Longitudinal MRI findings in suspected neuro-Behçet's disease: A case report - (:unkn) unknown (My University, 2006)
We have presented a case who took the diagnosis of probable neuro-Behçet's disease that was first presented with neurological sign and symptoms and showed spontaneous remission during the cranial magnetic resonance imaging follow-up. Involvement of the central nervous system usually follows systemic manifestations of Behçet's disease by months to years but as the initial future is only 5% of cases. Some patients develop neuro-Behçet simultaneously with or prior to the full-blown picture of Behcet's disease and this may cause confusion in the diagnosis. The neuroradiological features are well demonstrated in neuro-Behçet's disease. Experience reveals that magnetic resonance imaging is more sensitive than computerized tomography in detecting abnormalities in neuro-Behçet's disease. Most diffusely involved region is mesodiencephalic union and secondly pontobulber region.This case suggests that abnormal magnetic resonance findings in isole neuro-Behçet's disease are potentially reversible and that radiographic improvement parallels clinical improvement.
Keywords: Behçet's disease; Magnetic resonance imaging; Neurologic involvement